SYNTHESIS OF Na-A ZEOLITE FROM NATURAL ZEOLITES - Sariman Sariman (Puslitbang tekMIRA, 2005)
Conversion of natural zeolites into Na-A zeolite by the two-step method has been achieved. Synthesis process was conducted at hydrothermal condition 90° and 100° C using alkaline silicates as silica source aluminate as alumina source. The silica was derived from zeolitic tuff and the sodium aluminate was obtained from chemical reagent. Dissolution on zeolitic tuff was made in order to obtain supernatant, Na2SiO3.nH2O. Reaction time for the synthesis ranged from 0.5 – 4 h. It is found that SiO2/Al2O3 molar ratio of 1.6, Na2O/SiO2 molar ratio of 4.41, and Na2O/H2O molar ratio of 60.70, and crystallization time of 4 h give maximum crystallinity. XRD and SEM showed that Na-A zeolite synthesis begins after 1 h and reaches its crystallization maximum. Then Na-A is substituted by Na-X and hydroxysodalite (HS) zeolite. The XRD pattern and SEM image show that microtextural are comparable to the reputed zeolite commercial.